Analisis Rantai Pasok Kopra di Kecamatan Kempas Kabupaten Indragiri Hilir - Megawati Megawati; Farida Hanum Hamzah; Fajar Restuhadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This research aims to analyze supply chain flows, marketing channels, marketing margins, marketing share, marketing efficiency and find out the most efficient marketing network for copra commodities in Kempas District, Indragiri Hilir Regency. The research method used is descriptive qualitative including supply chain flow analysis and quantitative descriptive by calculating marketing margin, marketing share and marketing efficiency. Respondents in this study were 5 farmers, 3 collectors and 1 wholesaler. Respondents in this study were 5 farmers, 3 collectors and 1 wholesaler. The results showed that the copra supply chain in Harapan Tani Village, Kempas District, Indragiri Hilir Regency, exist 2 supply chain networks, network 1: farmers - collectors traders and network 2: farmers - collectors - wholesalers, and 3 streams managed, product flow, flow of money and flow of information. Network I, farmer’s have a marketing margin was6.066 IDR, the value of farmer shareis 66,73%, and the value of marketing efficiency is 23,72%.  Network II, farmer’s have a marketing margin was6.200 IDR, the value of farmer shareis 66,24%, and the value of marketing efficiency is 25,35%.  Collectors traders have a marketing margin of 4.867 IDR and the value of farmer shareis 73,50%. Keywords: copra, supply chain, marketing margin, marketing efficiency, marketingshare